1985
DOI: 10.1042/cs0680605
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of indomethacin on systemic and splanchnic haemodynamics in portal hypertensive rats

Abstract: Portal hypertension was produced experimentally in rats by partial constriction of the portal vein. Twelve rats were injected daily with indomethacin, 4 mg/kg body weight, and 12 with the vehicle (80% ethanol, 0.5 ml/day). There were no differences in portal-systemic shunts nor systemic or splanchnic haemodynamics between indomethacin-treated and untreated rats. These results suggest that cyclo-oxygenase products do not play a significative role in haemodynamic alterations shown by portal-ligated rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Concerning the haemodynamic effects of prostacyclin inhibition in portal hypertensive states, discrepant results have been obtained. Blockade of cyclooxygenase by indomethacin resulted in amelioration of the hyperdynamic circulation in portal-hypertensive rabbits [15,46]; however, this finding was not reproduced in portal hypertensive rats [47]. Similar to bleeding PVL rats [23], in this study we found that treatment with indomethacin in bleeding BDL rats seemed to create an insignificant trend to reduce mean arterial pressure.…”
Section: Discussioncontrasting
confidence: 54%
“…Concerning the haemodynamic effects of prostacyclin inhibition in portal hypertensive states, discrepant results have been obtained. Blockade of cyclooxygenase by indomethacin resulted in amelioration of the hyperdynamic circulation in portal-hypertensive rabbits [15,46]; however, this finding was not reproduced in portal hypertensive rats [47]. Similar to bleeding PVL rats [23], in this study we found that treatment with indomethacin in bleeding BDL rats seemed to create an insignificant trend to reduce mean arterial pressure.…”
Section: Discussioncontrasting
confidence: 54%
“…Blockade of cyclooxygenase by indomethacin results in a significant amelioration of the hyperdynamic circulation in portal-hypertensive rabbits (23,44); however, this finding was not reproduced in portal-hypertensive rats (45). In the current study treatment with indomethacin in bleeding PVL rats seemed to create a trend to reduce mean arterial pressure and portal pressure, although it did not reach a significant level.…”
Section: Discussionmentioning
confidence: 67%
“…Flurbiprofen treatment alone did not produce any significant change in the heart rate or mean arterial pressure in cirrhotic rats. At this dose, the anti‐inflammatory activity of this compound has been demonstrated in rats 23,45,46 . In contrast, a dramatic decrease in the mean arterial pressure was observed in cirrhotic rats after flurbiprofen and LPS administration, which may be explained by the additional deleterious hemodynamic effects of LPS and the gastrointestinal damage caused by flurbiprofen.…”
Section: Discussionmentioning
confidence: 86%